2011
DOI: 10.1002/jcla.20482
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of 55,769 HbA1c EQA results obtained from professional laboratories and medical offices participating in surveys organized by two European EQA centers over a nine‐year period

Abstract: External Quality Assessment (EQA) is an essential tool for laboratories to monitor the performances of their analyses. It also allows a comparison of methods and types of laboratories (professional laboratories vs. medical offices). We, therefore, compared 55,769 HbA1c EQA results obtained between 1999 and 2008 by laboratories participating in EQA schemes organized by two European centers, Switzerland (center 1) and France (center 2). We used simple, nonparametrical statistics suited to EQA results to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…However, in another study, the two groups showed similar performance. [ 19 ] Consistent with these results, more laboratories scored as “improvement needed” in the “BIO-RAD” group compared with those in the “TOSOH” and “ARKRAY” groups. Only one laboratory in the “enzymatic method” group was scored as “improvement needed”, showing poor precision performance.…”
Section: Discussionsupporting
confidence: 54%
“…However, in another study, the two groups showed similar performance. [ 19 ] Consistent with these results, more laboratories scored as “improvement needed” in the “BIO-RAD” group compared with those in the “TOSOH” and “ARKRAY” groups. Only one laboratory in the “enzymatic method” group was scored as “improvement needed”, showing poor precision performance.…”
Section: Discussionsupporting
confidence: 54%